Describimos las características de los espacios urbanos y rurales de mi localidad - Burga Vega, Elka Patricia (2020)
The purpose of the present professional proficiency research is to develope my learning_x000D_ session named “Describe the characteristics of the urban and rural spaces of your locality_x000D_ directed to fourth grade elementary school students of the municipal school educational_x000D_ institution of Trujillo city._x000D_ The professional proficiency research, consists in a learning session design, in the social_x000D_ area, in the proficiency that responsibly manages space and environment, which presents the_x000D_ purpose of develope a demonstrative session, displaying learning teaching strategies,_x000D_ similarly, using printed media and educational materials, in order to allow students to_x000D_ develop and increase their knowledge about the area previously mentioned, so they can_x000D_ accomplish those knowledge into practice, by solving multiple situations in the daily life._x000D_ In the session development, the students are given all the facilities and corresponding_x000D_ monitoring, so students have full confidence and autonomy in the acquisition of new_x000D_ knowledge, so that at the end of the session, they may be able to apply everything they have_x000D_ learned through their presentations.